The Role of Educational Leadership of School Principals in Enhancing the Academic Performance of Teachers and Students - Al-Khalidi, Mariam (Journal of Ecohumanism, 2025)
This study examines the role that the educational leadership of school principals has on improving the academic achievement of teachers and students in schools in Jordan. A quantitative descriptive correlational design was used, and a sample of 200 teachers was used to attain data on their characteristics through a structured questionnaire consisting of 3 main domains, namely, educational leadership practice by principals, academic performance of teachers, and students. Descriptive statistics showed that there is a high level of educational leadership among school principals (overall mean = 4.08), with the most prominent practices being communicating school vision and creating a good learning environment. Results also showed an excellent level of academic achievement of teachers and students (overall mean = 4.03). Pearson correlation analysis revealed a strong and statistically significant linear correlation between educational leadership and academic performance (r = 0.71, p < 0.001), and this correlation shows that improvements in practices of educational leadership are related to improvements in academic outcomes. The findings add to the international evidence of the profound but indirect impact of leadership on the quality of teaching and student learning through support, motivation, and professional development. The study suggests building up the system of rewards and recognition, increasing the data-driven leadership education, and investing in the professional development to keep up with high academic performance in schools.